Tectonic Evolution and Continental Fragmentation of the Southern West Australian Margin - Joanne Whittaker; Jacqueline Halpin; Williams, SE; Hall, LS; Gardner, R; Kobler, ME; Daczko, NR; Muller, RD (2013)
Continental rocks dredged in 2011 show that the Batavia Knoll and Gulden Draak Knoll, two prominent bathymetric features located ~1600 km offshore Perth, are micro-continents. Plate tectonic modeling reconstructs the pre-rift position of these knolls to the north and south of the Naturaliste Plateau, respectively. The Batavia Knoll was conjugate to part of the northern Naturaliste Plateau, while the Gulden Draak Knoll was conjugate to the western Bruce Rise, Antarctica. Here, we compare basement rocks, patterns of sedimentation, volcanism and structure on the better studied Naturaliste Plateau, Mentelle Basin and Bruce Rise with newly collected data from the knolls. Significant volumes of metamorphic and granitic basement rocks were dredged from both the Batavia and Gulden Draak knolls. Preliminary geochronological and geochemical analyses show that these rocks are continental in nature and include protolith granitoids that were emplaced during the Archaean (~2850 Ma) and the Mesoproterozoic (~1290–1200 Ma) (Gulden Draak Knoll), and during the Early Palaeozoic (~540–530 Ma) (Batavia Knoll). All metamorphic rocks were invariably reworked during the Kuunga Orogeny (~550–500 Ma) during the final assembly of Gondwana. Sediment accumulations are generally relatively thin (up to a few hundred meters) on all the continental fragments, with the exception of NNE to NE oriented rift basins with up to ~2 km of sediments. Sedimentary rocks, predominantly sandstones were dredged from adjacent to the interpreted rift basin locations on both the Batavia and Gulden Draak knolls. Volcanic/intrusive material has been interpreted on the northern flank of the Naturaliste Plateau from seismic profiles, but no basalts were found in either of the Batavia Knoll dredges. Extensive volcanism has also been interpreted on both the Naturaliste Plateau and Bruce Rise. Volcanic material was dredged in one of two sites on the Gulden Draak Knoll, and geophysical data may support the presence of an igneous domain. The structural, volcanic and ...